An Ecology of Transformative Learning: A Shift From the Ego to the Eco. (January 2020) - Bainbridge, Alan; Del Negro, Gaia
This article argues that the phenomenon of a genetic/cultural "adaptive-lag" is both the motive for the human predisposition to engage in transformative learning and the origin of anxiety and associated ego-defences that mitigate against the likelihood of transforming epistemic assumptions. Dodds' (2011) ecopsychoanalytic interpretation of Winnicott's concept of a holding environment provides the conditions to reduce the impact of ego-defences by containing anxiety and therefore supporting the transformation of epistemic assumptions. Such holding environments are conceived to extend from intimate familial and social relationships to include wider ecological interconnectedness. Narratives, literature, and evidence from clinical psychedelic drug studies highlight how an increased sensitivity towards the natural nonhuman world diminishes ego-defences, enhancing the possibility for transformative learning. The implications for educational settings are that complex and difficult learning should not be ameliorated and that conditions enabling learners to recognize and manage their own anxieties will enhance epistemic transformation.